The role of Capon in multiple myeloma - Yaodong Shen; Haiyan Liu; Siyu Gu; Ziwei Wei; Hong Liu (Tumor Biology)
Capon is a ligand protein of nitric oxide synthase 1. Recently, studies have shown that Capon is involved in the development of tumors. It is independent of the regulation of nitric oxide synthase 1 in this process. At the same time, studies have found that nitric oxide synthase 1 is expressed in multiple myeloma, but its role in the development and progression of myeloma remains unclear. In this study, we found that there was a different expression of Capon between the normal multiple myeloma cells and the adherent multiple myeloma cells. In the process of myeloma cell proliferation, the reduced expression of Capon reduces the arrest of the cell cycle in the G1 phase and promotes the proliferation of myeloma cells. Cell adhesion–mediated drug resistance is one of the most important factors, which affect the chemotherapy effect of multiple myeloma. If the expression of Capon is decreased, myeloma cells are adhered to fibronectin or bone marrow stromal cells (bone marrow mesenchymal stem cells). In addition, the sensitivity of the cell line to chemotherapeutic agents was reduced after silencing Capon in the myeloma cell line which was adhered to bone marrow mesenchymal stem cells. We also found that reduced expression of Capon resulted in the activation of the AKT signaling pathway. In conclusion, these results may be helpful in studying the role of Capon in multiple myeloma.